SEJARAH PERPUSTAKAAN BAIT AL-HIKMAH PADA MASA KEEMASAN DINASTI ABBASIYAH - Yanto Yanto (Fakultas Adab dan Humaniora UIN Raden Fatah, 2015)
Historically, Muslims have experienced the triumph of civilization, especially during the Abbasid dynasty. This achievement can not be released with the message of Islam which has always encouraged its followers to have extensive knowledge. It is also recognized by some of the Abbasid rulers, so that the scientific development of great concern. Therefore, several scientific institutes are built in order to realize these goals. One of the institutions that are Bait al-Hikmah. This institution, as well as educational institutions, also an institute library. With a historical overview, this paper seeks to analyze the role of Bait al-Hikma library during the Abbasid dynasty. Because it deals with the science of libraries, then difoukuskan study on the management of Bait al-Hikma library, so the library has a major role in the triumph of civilization during the Abbasid Dynasty.